2020
DOI: 10.1097/sap.0000000000002584
|View full text |Cite
|
Sign up to set email alerts
|

Does Water-Jet Force Affect Cryopreserved Adipose-Derived Stem Cells? Evidence of Improved Cell Viability and Fat Graft Survival

Abstract: Background Adipose tissue harvested by liposuctions is an available source of adipose-derived stem cells (ASCs). Water-jet–assisted liposuction is a favorable method for fat collection with little mechanical damage. This study aimed to investigate whether or not the water-jet–assisted liposuction made a difference in the biological characteristics of cryopreserved ASCs and fat graft survival in cell-assisted lipotransfer. Methods Human lipoaspirates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Earlier studies have shown a variance of 10% −80% survival of fat grafts that are not augmented with ASCs. The water jet technique has shown promising results with regard to cell viability [12][13][14] and when used in the absence of cell supplementation, it is possible to achieve better fat survival using the water jet technique when compared with manual isolation [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown a variance of 10% −80% survival of fat grafts that are not augmented with ASCs. The water jet technique has shown promising results with regard to cell viability [12][13][14] and when used in the absence of cell supplementation, it is possible to achieve better fat survival using the water jet technique when compared with manual isolation [14] .…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can be easily isolated from different tissues. Even if bone marrow stem cells are still the MSCs used most often, the invasive procedure to isolate the bone marrow makes it more difficult and more stressful for the donors [52], compared with the use of adipose stem cells that can be easily isolated from liposuction [53,54]. In addition, the number of isolated adipose stromal cells from the liposuction can be 50,000 times higher than the number of bone marrow stem cells isolated from the bone marrow [55][56][57].…”
Section: Introductionmentioning
confidence: 99%